2021
DOI: 10.1002/tea.21728
|View full text |Cite
|
Sign up to set email alerts
|

School subjects' synergy and teacher knowledge: Do biology and chemistry teachers benefit equally from their second subject?

Abstract: German preservice teachers always study two teaching subjects instead of only one. This offers an almost paradigmatic approach for the investigation of effects of specific subject combinations on professional competence. So far, few studies focused on potential beneficial effects or risks on preservice teachers' motivational orientations, beliefs, and professional knowledge. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…As expected, the group of pre-service teachers who combined two science subjects achieved significantly higher TSR-EBI scores than the groups with other subject combinations. Hence, our finding is in line with, for example, the study by Welter et al ( 2022 ), which also suggested synergistic effects of specific combinations of pre-service teachers' majors on the development of their professional competence. However, whether these higher TSR-EBI scores are actually reflected in improved long-term teaching success must first be investigated by means of appropriate longitudinal assessments before any recommendations for action can be derived.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As expected, the group of pre-service teachers who combined two science subjects achieved significantly higher TSR-EBI scores than the groups with other subject combinations. Hence, our finding is in line with, for example, the study by Welter et al ( 2022 ), which also suggested synergistic effects of specific combinations of pre-service teachers' majors on the development of their professional competence. However, whether these higher TSR-EBI scores are actually reflected in improved long-term teaching success must first be investigated by means of appropriate longitudinal assessments before any recommendations for action can be derived.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, intra-individual differences in self-efficacy beliefs might be found among teachers who teach multiple subjects (Menon and Sadler, 2017 ; Al Sultan, 2020 ). In addition, however, inter-individual differences between teachers of different (groups of) subjects may also be expected (Riggs and Enochs, 1990 ; Welter et al, 2022 ). In this respect, it is plausible, for example, that teachers who teach comparatively abstract subjects such as chemistry or physics have a different teaching-related self-efficacy than teachers who teach a physical subject such as sports, e.g., due to varying predictability of their teaching and/or of sources of student difficulties (Raudenbush et al, 1992 ; Ross et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This synergy does not only expand the university's knowledge to create benefits and add value in terms of the efficient use of shared resources, but also creates guidelines or methods for working together as part of a collaborative process in order to develop the quality of learners by focusing on working together with the same goal-success in working. Even though the learners are from different fields or have different roles, they can work together remarkably in order to expand the results in such a way as to create mutual benefits and reinforce results to a greater extent than either working alone or in a single field or by depending on a single set of expertise that acts alone (Welter et al, 2022) . This is consistent with the studies of educators over many generations.…”
Section: Discussionmentioning
confidence: 99%